A fast extremum-seeking approach for the methanisation of organic waste in an anaerobic bioreactor. Issue 1 (2019) - Vargas, Alejandro; Sepíuveda-Gálvez, Alfonso; Barrios-Pérez, Julián D.
Abstract: We consider the AM2 mechanistic mathematical model of an anaerobic bioreactor, where the controlled input is the dilution rate and the measured output is the methane outflow rate. We show that a control strategy based on switching between two dilution rates is able to bring the trajectories close to the optimal steady-state where the output is maximized; this is based on a recent result for designing a fast extremum-seeking controller. Experimental results from a laboratory-scale bioreactor treating agave bagasse hydrolysates are used to find model parameters and to show the appearance of the predicted phenomenon.